Corak Pemikiran Hukum Islam Hasbi Ash-Shiddieqy antara Purifikasi dan Modernisasi - Hedhri Nadhiran (Media Syari'ah, 2012)
This article aims to examine the Islamic legal thought developed by Hasbi Ash-Shieddieqy between purification and modernization. Studies show that Hasbi is consistently as a modernist. This conclusion is based on two cases that raised issues of worship, which is about the Friday prayers and zakat measurement. In understanding these two issues, Hasbi not solely used naqli (revealed) arguments, but also ‘aqli (reason arguments).